The Relationship between Board Gender Diversity in Brazilian Companies and Adhesion to the Carbon Efficient Index - Firmino, Anderson Luís; Peixoto, Fernanda Maciel (Advances in Scientific and Applied Accounting, 2023)
Objectives: This study investigated the relationship between the presence of women in the Boards of Directors (BDs) and company adhesion to the Carbon Efficient Index (ICO2). Additionally, the study investigated whether company adhesion to the Corporate Sustainability Index (ISE) increases the likelihood of adhesion to the ICO2. Method: The study adopted the logistic regression method, given that the dependent variable (ICO2) is binary. The sample included Brazilian companies that are part of the BrX100, and the study period was from 2011 to 2021. The study segmented the companies into two sub-samples: one group composed of potentially more polluting companies, and one group composed of potentially less polluting companies. Results: We found a positive relationship between the presence of women in BDs and adhesion to ICO2 for the group composed of more polluting companies, and when the BD was presided by a woman, this relationship happened in all subdivisions of the sample. The findings also indicated that companies that are more leveraged and have greater liquidity, greater market value, and more assets, are more likely to be part of the ICO2. Contributions: The major contribution of this study is the classification of the sample into different groups of sectors related to gas emissions. This study is in line with three of the UN Sustainable Development Goals (SDGs): gender equality, innovation and action against climate change. In addition, the study is relevant because it showed that the protagonism of women in BDs leads to sustainable, environmentally efficient practices.